Does Environmental, Social, and Governance Drive the Sustainability of Multinational Corporation’s Subsidiaries? Evidence From Korea - Kim, Jangsoon; Cho, Eunho; Okafor, Collins E.; Choi, Donseung (Frontiers in Psychology, 2022)
We examined the relations between environmental, social, and governance (ESG) activities and the performance of subsidiaries of multinational corporations (MNCs). We further investigated the moderating effect of market-oriented organizational culture on the relationship between ESG and performance. Employing generalized least square regression analysis using survey data, we show that ESG activities of MNC subsidiaries are positively associated with financial and non-financial performance. These results suggest that ESG improves the financial and non-financial performance of subsidiaries. The test for the moderating effect of the market-oriented organizational culture shows that it weakens the positive relationship between ESG activities and financial performance. This could be due to the incongruous nature of the short-term focus of a market-oriented organizational culture versus the long-term orientation of the sustainability of ESG activities.